Screening for resistance against major lepidopteran and stem weevil pests of amaranth in Tanzania - Othim, S.T.O.; Srinivasan, R.; Kahuthia-Gathu, R.; Dubois, T.; Dinssa, F.F.; Ekesi, S.; Fiaboe, K.K.M. (2018)
Insect pests pose major challenges to optimum productivity of amaranth in Africa and Asia. The use of insecticides is the main control strategy, but is expensive and may pose health and environmental concerns, especially if proper care is not taken. Host plant resistance offers a cheap and sustainable pest management alternative. Open field experiments were conducted during two cropping seasons in 2016 and 2017 to screen 35 amaranth accessions and lines for resistance to leaf-webbers and stem weevils. The diversity (H) of lepidopteran defoliators and their parasitoids on each accession ranged from 0.00 to 1.57 and 0.00 to 1.65, respectively during the long rainy season and from 0.00 to 1.58 and 0.00 to 1.01 in the short rainy season. Accessions VI036227, RVI00027, VI054569, VI033487, VI044432, VI048076, VI049639, VI049530 and VI049698 had high levels of pest resistance with significantly lower infestations (≤ 11.11 ± 2.14%) and damage (≤ 68.06 ± 3.90%) by leaf-webbers and leaf-worms. Stem weevil infestations ranged from 68.70 ± 2.0% to 90.42 ± 1.0% during the long and short rainy seasons, respectively. Accessions VI047517-B, VI036227 and VI056563 had the least stem weevil infestations (< 62.5%) but differences among accessions for damage incidences were non-significant. Parasitism was observed in all the accessions except seven of them. Amaranth accessions exhibiting pest resistance or at least non-preference traits are important for success of breeding programs. The importance of deploying such accessions to breed for improvement of susceptible lines (by introgression) or their release to farmers, if they have desirable horticultural traits that are required by vegetable producers and consumers, for effective management of amaranth pests is also discussed.